Талаба-ёшларнинг соғлом турмуш тарзини шакллантиришда соғломлаштирувчи жисмоний машқларнинг тутган ўрни. - Коссе, Коссе (FILOLOGIYA UFQLARI JURNALI, 2022)
The article illustrates minds about knowledge and experience needing in social protection. Helping to population and improving extension in sphere of service and tourism. Some ways and thoughts for decision tasks and problems.